On Ovarian Tissue Transplantation and the Metaphysics of Self-Recognition: A Response to Paul Lauritzen and Andrea Vicini - Austriaco, Nicanor Pier Giorgio (Theological studies, 2012)
To resolve questions regarding ovarian tissue transplantation, the author proposes a metaphysical theory positing that the common ensoulment shared by all the cells in a woman's body is manifested primarily in her immune system's ability to distinguish her own cells from those of another. The author therefore suggests that human procreation, to be morally licit, has to involve the giving of one's gametes, defined, not by their genetic constitution, but by their being part of the immunologically defined self given in the mutual self-gift that is conjugal love.